1991
DOI: 10.1073/pnas.88.7.2922
|View full text |Cite
|
Sign up to set email alerts
|

Retroviral sequences related to human T-lymphotropic virus type II in patients with chronic fatigue immune dysfunction syndrome.

Abstract: Chronic fatigue immune dysfunction syndrome (CFIDS) is a recently recognized illness characterized by debilitating fatigue as well as immunological and neurological abnormalities [Straus, S. E. (1988) J. Inf. Dis. 157, 405412]. Once thought to be caused by Epstein-Barr virus, it is now thought to have a different but unknown etiology. We evaluated 30 adult and pediatric CFIDS patients from six eastern states for the presence of human T-lymphotropic virus (HTLV) types I and II by Western immunoblotting, polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(38 citation statements)
references
References 26 publications
1
36
1
Order By: Relevance
“…Independent confirmation and validation in multiple laboratories, ideally in blinded studies, would be needed to make such claims. It should be noted that the involvement of a retrovirus (specifically HTLV-II) in chronic fatigue syndrome was first suggested in 1991 [46], although it was never confirmed and eventually forgotten.…”
Section: Xmrv In Chronic Fatigue Syndromementioning
confidence: 97%
“…Independent confirmation and validation in multiple laboratories, ideally in blinded studies, would be needed to make such claims. It should be noted that the involvement of a retrovirus (specifically HTLV-II) in chronic fatigue syndrome was first suggested in 1991 [46], although it was never confirmed and eventually forgotten.…”
Section: Xmrv In Chronic Fatigue Syndromementioning
confidence: 97%
“…21 In this study, retroviral risk factors were absent, and results of an analysis of other HTLV-11 gene sequences were negative, indicating that prototypic HTLV-11 could not be responsible for the results. These sequences may reflect the presence of a novel human retrovirus or a reactivated endogenous virus.…”
Section: New Directionsmentioning
confidence: 69%
“…4 In 1991, viral sequences from human T-lymphotropic virus type 2 were isolated in patients with CFS. 18 Soon thereafter, independent groups in the United States and the United Kingdom were unable to replicate the results. 19,20 Several reports have suggested that contamination of human cells by mouse DNA can lead to the false detection of XMRV, 21Y23 and another showed a commercial real time-PCR test kit used to detect a partial gag region of XMRV was contaminated with small traces of endogenous murine leukemia virus.…”
Section: Evidence Against Association Of Xmrv Infection and Cfsmentioning
confidence: 93%